2019
DOI: 10.1038/s41416-019-0692-2
|View full text |Cite
|
Sign up to set email alerts
|

Syncope as a sign of occult cancers: a population-based cohort study

Abstract: Background We examined if syncope was a marker of an occult cancer by comparing the risk in patients with a syncope episode with that of the general population. Methods Using Danish population-based medical registries, we identified all patients diagnosed with syncope during 1994–2013 and followed them until a cancer diagnosis, emigration, death or end of follow-up, whichever came first. We computed cumulative risks and standardised incidence ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…Only slightly more than one in a thousand patients in the group with syncope were diagnosed with a brain tumor in the 6-month period, and this figure was even lower than one in three thousand in the group without syncope. These results are consistent with the findings of Lorenzen et al, who's large population-based cohort study investigated whether syncope was a marker for hidden cancer, showing an increased but relatively low cumulative risk of brain tumor over a six-month period for a cohort of syncope patients [20].…”
Section: Interpretation Of Findingssupporting
confidence: 91%
See 2 more Smart Citations
“…Only slightly more than one in a thousand patients in the group with syncope were diagnosed with a brain tumor in the 6-month period, and this figure was even lower than one in three thousand in the group without syncope. These results are consistent with the findings of Lorenzen et al, who's large population-based cohort study investigated whether syncope was a marker for hidden cancer, showing an increased but relatively low cumulative risk of brain tumor over a six-month period for a cohort of syncope patients [20].…”
Section: Interpretation Of Findingssupporting
confidence: 91%
“…As possible mechanisms of an association between brain tumors and syncope, the authors of the study identified, among other factors, compression of blood vessels, infiltration of the vagus and glossopharyngeal nerves, and infiltration of the brain areas relevant for cardiovascular functions, as well as tumor-induced anemia and tumor-induced venous thromboembolism, all of which can cause cerebral hypoperfusion and, thus, result in syncope [ 20 ]. Furthermore, the association between syncope and brain tumor diagnosis was only significant in the age groups 61–70 years and >70 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation